(untitled) (Research, Society and Development, 2020)
This study aims to assess, through a retrospective study, the electrocardiographic parameters and major changes in rhythm in elderly dogs and cats attended by a veterinary cardiology service. With the increase in longevity of domestic dogs and cats, greater care for the health of these species is necessary, especially in elderly animals. Early diagnosis for different rhythm disorders and disorders is extremely important for the treatment of diseases of the cardiovascular system. Thus, it is essential to understand aspects related to the complementary exam modalities associated with the clinical cardiological exam. The electrocardiogram is a low-cost, non-invasive test, capable of diagnosing a range of heart diseases and even evidence of other systemic disorders. Medical records and electrocardiographic record of 150 animals were evaluated, including dogs and cats, observing the fact of senile age as an inclusion criterion. Sinus arrhythmia, sinus rhythm and sinus bradycardia were the most prevalent rhythms. The average heart rate was another parameter evaluated and it was shown to decrease with advancing age. With the present study, it is noted the importance of electrocardiographic examination in elderly dogs and cats and the need for further studies with larger populations that aim to determine normal parameters for animals of each species in this age group.